The Influence of Social Media Marketing Activities and Service Quality on Consumer Satisfaction at the Rava Nailart Business in South Lampung - Dora Rinova; Nadia Sepriani (Cita konsultindo, 2024)
This research aims to analyze the influence of social media marketing activities as well as service quality on consumer satisfaction at the Rava NailArt business in South Lampung. In facing the ever-growing era of digitalization, beauty businesses such as Rava NailArt encounter new challenges and opportunities in expanding their market reach. Social media marketing activities have become an essential marketing strategy, allowing companies to interact with potential consumers, promote products, and build brand image. This factor is considered crucial in supporting the growth of local beauty businesses amidst increasingly fierce competition. Apart from social media marketing activities, service quality also plays an important role in influencing consumer satisfaction. In service industries such as beauty salons, customer experience and quality service can be a key determinant of retaining and attracting consumers. Therefore, this research not only explores the impact of social media marketing activities on consumer satisfaction, but also assesses the extent to which service quality can shape consumers' positive perceptions of Rava NailArt's business. This research method uses a quantitative approach which collects data through questionnaires and then distributes them to Rava NailArt consumers. Regression analysis will be used to measure the extent to which social media marketing activities and service quality contribute to consumer satisfaction. The results of this research are that social marketing activities and service quality have a significant effect on consumer satisfaction.